Quantitative Assessment of Sialo‐Glycoproteins and N‐Glycans during Cardiomyogenic Differentiation of Human Induced Pluripotent Stem Cells. (13th June 2017) - Konze, Sarah A.; Cajic, Samanta; Oberbeck, Astrid; Hennig, René; Pich, Andreas; Rapp, Erdmann; Buettner, Falk F. R.
Abstract: Human induced pluripotent stem‐cell‐derived cardiomyocytes (hiPSC CMs) may be used in regenerative medicine for individualized tissue transplants in the future. For application in patients, the generated CMs have to be highly pure and well characterized. In order to overcome the prevalent scarcity of CM‐specific markers, we quantitatively assessed cell‐surface‐exposed sialo‐glycoproteins and N‐glycans of hiPSCs, CM progenitors, and CMs. Applying a combination of metabolic labeling and specific sialo‐glycoprotein capture, we could highly enrich and quantify membrane proteins during cardiomyogenic differentiation. Among them we identified a number of novel, putative biomarkers for hiPSC CMs. Analysis of the N‐glycome by capillary gel electrophoresis revealed three novel structures comprising β1, 3‐linked galactose, α2, 6‐linked sialic acid and complex fucosylation; these were highly specific for hiPSCs. Bisecting GlcNAc structures strongly increased during differentiation, and we propose that they are characteristic of early, immature CMs. Abstract : Differentiating hearts : Human induced pluripotent stem cells, cardiac progenitors, and stem‐cell‐derived cardiomyocytes were analyzed and compared at the sialo‐glycoproteomic, proteomic, and N‐glycomic levels. This approach led to the identification of novel potential biomarkers for these cell types.